INTEGRATION OF THE CODE OF ETHICS OF JUDGES IN THE IMPLEMENTATION OF PERMA NO. 1 OF 2024: THE INFLUENCE OF JUDICIAL INDEPENDENCE IN IMPLEMENTING RESTORATIVE JUSTICE - Milda Istiqomah; Reni Ringgita Laia (CV. RADJA PUBLIKA, 2025)
Supreme Court Regulation of the Republic of Indonesia No. 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice provides guidelines for judges in implementing restorative justice in court. This regulation requires an active role for judges as peace facilitators, which raises questions regarding the independence of judges. This study aims to analyze how the independence of judges and the code of ethics of judges are integrated in the implementation of Perma No. 1 of 2024, especially in maintaining the independence of judges in the restorative justice process. This study uses a conceptual approach, a legislative approach and a case approach. The results of the study indicate that the independence of judges and the code of ethics of judges are important foundations in the implementation of Perma No. 1 of 2024. The independence of judges guarantees objectivity and justice in the peace process, while the code of ethics guides judges to act fairly, wisely and with integrity. Judges must always adhere to the principle of independence and ethical values, even though they are required to play an active role in the peace process. This study provides suggestions on the importance of socialization and training for judges regarding Perma No. 1 of 2024 and the code of ethics in the context of restorative justice, as well as strengthening internal and external supervision of judges in the implementation of restorative justice.